DESIGNING ENGLISH WORKSHEET FOR THE STUDENTS OF ISLAMIC JUNIOR HIGH SCHOOL IN JAMBI - Nurhasanah, Amalia; Mahmudah, Faiqah; Winarti, Muncar (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2023)
This article aims at elaborating the process of designing a worksheet to teach English specifically speaking and writing skills for the students of an Islamic Junior High School in Jambi. This was a research and development inquiry in which the researchers applied Dick and Carey’s model (in Gall and Borg, 2003). List of questions for interview, questionnaires, observation checklist, and documentation were used as instruments to obtain the data. Based on the need analysis, it was found that the English materials expected by the eighth grade students were: (a) picture-based material which were colorful and attractive, (b) simple English texts with understandable questions, (c) well-understood instruction, and (d) using familiar words. The final design of the material consisted of three chapters with different themes.